Nitrogen Fertilization of Strawberry Cultivars: Is Preplant Starter Fertilizer Needed? - Bielinski M. Santos; Alicia J. Whidden (EDIS, 2007)
HS-1116, a 2-page illustrated fact sheet by Bielinski M. Santos and Alicia J. Whidden, summarizes for growers the results of studies conducted to determine whether using preplant starter N fertilization increases strawberry early and total yield. Published August 2007.